(untitled) (Al-Mukhtar Journal of Economic Sciences, 2022)
This study aims at identifying the impact of using cloud accounting technique on the financial performance of the Libyan commercial banks. To achieve the objective of this study, the researcher has followed the descriptive analytical approach due to its suitability to the nature of the study. The researcher has also designed a questionnaire consisting of (30) paragraphs which is submitted to the study population consisting of the Libyan commercial banks located in the cities of Sirte & Ras Lanuf, numbering (10) banks. (50) Questionnaire have been distributed to the study population that is represented in (bank managers and their associates, heads of departments and some other employees); 47 of them were returned and all questionnaires were analyzable. The Statistical Package for the Social Sciences software program "SPSS" was used to analyze the data collected and test hypotheses. The study concluded, inter alia, that the application of cloud accounting technique contributes to improving the financial performance of the Libyan commercial banks given the fact that it helps in (reducing the costs, risks and time, achieving flexibility and ease of access to data and information).